2011
DOI: 10.12968/ijtr.2011.18.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and engagement among physiotherapists

Abstract: Monica Martinussen, Per-Christian Borgen, Astrid Marie Richardsen Aims: This article describes a study examining predictors of burnout and engagement, including job demands, job resources and Type A behaviour, in a sample of Norwegian physiotherapists (N = 244). Methods: This study measured demographic and work characteristics, job demands, job resources, burnout, work engagement and type A behaviour for all members of the sample. Findings: Both job demands and resources predicted burnout and engagement, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
2
8
0
2
Order By: Relevance
“…A study of physiotherapists 289 found that type A behaviour, including high levels of achievement striving and low levels of impatience-irritability, were associated with higher levels of engagement. Sonnentag et al, 96 in a two-wave survey of workers in a non-profit organisation offering services to people with special needs, found that low negative affectivity and low levels of engagement at time 1 were associated with work engagement at time 2 but that levels of psychological detachment did not contribute to the prediction of engagement.…”
Section: Individual Psychological Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of physiotherapists 289 found that type A behaviour, including high levels of achievement striving and low levels of impatience-irritability, were associated with higher levels of engagement. Sonnentag et al, 96 in a two-wave survey of workers in a non-profit organisation offering services to people with special needs, found that low negative affectivity and low levels of engagement at time 1 were associated with work engagement at time 2 but that levels of psychological detachment did not contribute to the prediction of engagement.…”
Section: Individual Psychological Statesmentioning
confidence: 99%
“…Hu et al 203 ) but others found no association 284 or a positive association. 289 Single studies have been conducted on other aspects of job design: Bamford et al 113 found a positive link between areas of work life and engagement; Gorter and Freeman 284 found that perceptions of doing the job well for patients, the joy of working and results were linked with engagement for dentists; Hornung et al 110 found that task-idiosyncratic deals were indirectly linked with engagement through complexity, control and hindrance; Taipale et al 115 found autonomy and engagement to be linked; and Weigl et al's 300 time-lagged survey found job control, working relationships and active coping were linked with engagement. In two cross-sectional studies, 145,236 structural empowerment was linked with engagement.…”
Section: Individual Psychological Statesmentioning
confidence: 99%
“…However, previous studies have not shown consistent results, and it is difficult to distinguish specific factors that cause therapist burnout. Working hours is one such organisational factor, with inconsistent results that have shown positive relations with burnout (Martinussen, Borgen, & Richardsen, ) but also negative relations with burnout (Rosenberg & Pace, ). Caseload and income also showed both negative and positive relationships with burnout, but the strength of the relationships was weak, usually ranging from −0.20 to 0.09 (Acker, ; Wallace, Lee, & Lee, ; Wilkerson, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies underlining physiotherapists' susceptibility to burnout syndrome (4,(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%